2020
DOI: 10.1155/2020/8841983
|View full text |Cite
|
Sign up to set email alerts
|

When a Dead Patient Is Not Really Dead: Lazarus Phenomenon

Abstract: Lazarus phenomenon refers to autoresuscitation of a patient declared dead after cessation of cardiopulmonary resuscitation (CPR). The Lazarus phenomenon is rarely encountered and pathophysiology is not very well understood, but physicians need to be aware of this phenomenon. It is prudent that a physician leading a CPR effort waits for some time and monitors the patient further using blood pressure and electrocardiogram before confirming that a patient is actually dead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These studies showed that autoresuscitation may occur after five minutes of observation following terminated CPR, occurring up to 20 min after terminated CPR in one case report. 28 A large observational study supported these case report observations though important confounders were identified in the two autoresuscitation events occurring beyond five minutes of observation, leading to low certainty in the evidence. 7 One patient (autoresuscitation at six minutes) did not have the ventilation bag disconnected from the endotracheal tube, and another patient (autoresuscitation at eight minutes) had continuation of norepinephrine infusion after CPR cessation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These studies showed that autoresuscitation may occur after five minutes of observation following terminated CPR, occurring up to 20 min after terminated CPR in one case report. 28 A large observational study supported these case report observations though important confounders were identified in the two autoresuscitation events occurring beyond five minutes of observation, leading to low certainty in the evidence. 7 One patient (autoresuscitation at six minutes) did not have the ventilation bag disconnected from the endotracheal tube, and another patient (autoresuscitation at eight minutes) had continuation of norepinephrine infusion after CPR cessation.…”
Section: Discussionmentioning
confidence: 75%
“…Ten case reports (71%) described autoresuscitation events in a total of 11 patients following unsuccessful CPR. 28 – 30 , 33 – 39 Six patients had an out-of-hospital cardiac arrest (OHCA) 29 , 33 , 34 , 37 , 39 and five an in-hospital cardiac arrest. 28 , 30 , 35 , 36 , 38 Most patients were adults ( n = 10; age range, 25–79 yr).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them was cardiac arrest in the operating room during laparotomy in a 33-year-old patient who had previously had a ventriculoperitoneal shunt after meningioma surgery and now had an "acute abdomen" due to a ventriculoperitoneal shunt. Computed tomography of the head showed areas of acute infarction involving the brainstem and cerebellar hemispheres, as well as moderate enlargement of the ventricular system with left-sided intraventricular hemorrhage [43]. During the procedure, the patient developed bradycardia and asystole.…”
Section: The Latest Cases Of the Lazarus Phenomenonmentioning
confidence: 98%
“…Activities stopped, but after 30s, presence of a pulse was noticed. 10 So far 17 reported cases of Lazarus phenomenon in last 10 years are summarized in Table . Cases described include both in-hospital and out-of-hospital arrests.…”
Section: Notable Casesmentioning
confidence: 99%